Characteristics and Course of Enthesitis in a Juvenile Idiopathic Arthritis Inception Cohort. Issue 2 (29th January 2018) - Rumsey, Dax G.; Guzman, Jaime; Rosenberg, Alan M.; Huber, Adam M.; Scuccimarri, Rosie; Shiff, Natalie J.; Bruns, Alessandra; Feldman, Brian M.; Eurich, Dean T.; ,
Abstract : Objective: To describe the prevalence, associated characteristics, and course of enthesitis in a juvenile idiopathic arthritis (JIA) inception cohort. Methods: Canadian children newly diagnosed with JIA between 2005 and 2010 were categorized using International League of Associations for Rheumatology criteria at the 6‐month visit and followed in the Research in Arthritis in Canadian Children Emphasizing Outcomes (ReACCh‐Out) cohort for up to 5 years. The presence of entheseal tenderness on examination at 33 sites shown on a homunculus was recorded at 0, 6, 12, 18, 24, 36, 48, and 60 months after enrollment. Enthesitis was defined as entheseal tenderness at more than 1 site or on more than 1 occasion. Analyses consisted of descriptive statistics and linear mixed models for longitudinal data. Results: Of 1, 406 patients, 219 (16%) had enthesitis and, of those with enthesitis, 141 (64%) were classified as having enthesitis‐related arthritis (ERA). Children with enthesitis were more often older (10.7 versus 7.5 years), male (57% versus 31%), and with polyarthritis (57% versus 41%) and sacroiliac involvement (30% versus 4%). Entheseal tenderness was most frequent at the calcaneal plantar fascial insertion (39%), Achilles tendon insertion (31%), and tibial tuberosity (30%). The mean number of tender entheseal sites decreased in parallel with active joint counts. There was no difference in active joint counts over time in children with or without enthesitis ( P = 0.73). Conclusion: Enthesitis was observed in 16% of patients with JIA, but only two thirds were categorized as having ERA. Contrary to expectations, most children with enthesitis had polyarticular involvement. The course of enthesitis paralleled the course of active joint counts.